College students' virtual and in‐person drinking contexts during the COVID‐19 pandemic. (1st December 2022) - Hultgren, Brittney A.; Smith‐LeCavalier, Kirstyn N.; Canning, Jessica R.; Jaffe, Anna E.; Kim, Isabel S.; Cegielski, Victoria I.; Garcia, Tracey A.; Larimer, Mary E.
Abstract: Background: The COVID‐19 pandemic has resulted in pronounced changes for college students, including shifts in living situations and engagement in virtual environments. Although college drinking decreased at the onset of the pandemic, a nuanced understanding of pandemic‐related changes in drinking contexts and the risks conferred by each context on alcohol use and related consequences have yet to be assessed. Methods: Secondary data analyses were conducted on screening data from a large parent clinical trial assessing a college student drinking intervention ( N  = 1669). Participants across six cohorts (from Spring 2020 to Summer 2021) reported on the frequency of drinking in each context (i.e., outside the home, home alone, home with others in‐person, and home with others virtually), typical amount of drinking, and seven alcohol‐related consequence subscales. Results: Descriptive statistics and negative binomial regressions indicated that the proportion and frequency of drinking at home virtually with others decreased, while drinking outside the home increased from Spring 2020 to Summer 2021. Limited differences were observed in the proportion or frequency of individuals drinking at home alone or at home with others in‐person. Negative binomial and logistic regressions indicated that the frequency of drinking outside the home was most consistently associated with more alcohol‐related consequences (i.e., six of the seven subscales). However, drinking at home was not without risks; drinking home alone was associated with abuse/dependence, personal, social, hangover, and social media consequences; drinking home with others virtually was associated with abuse/dependence and social consequences; drinking home with others in‐person was associated with drunk texting/dialing. Conclusion: The proportion and frequency of drinking in certain contexts changed during the COVID‐19 pandemic, although drinking outside the home represented the highest risk drinking context across the pandemic. Future prevention and intervention efforts may benefit from considering approaches specific to different drinking contexts. Abstract : The COVID‐19 pandemic incited changes in environments for college students. Students across six cohorts (Spring 2020 – Summer 2021) reported frequency of drinking outside the home, home alone, home with others in‐person, and home with others virtually. Drinking at home virtually with others decreased, drinking outside the home increased, few changes for drinking home with others in‐person and home alone were observed. Drinking outside the home represented the highest risk drinking context for consequences, followed by drinking at home alone.